PERINTAH MEMERANGI NON MUSLIM DALAM HADIS: (Analisis Ma’ani al-Hadis dan Kontekstualisasinya) - A.M. Ismatulloh dan Haidir Rahman (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
There is a hadith which contains orders to fight adherents of other religions outside of Islam. The Hadith gives the impression of imposing Islam on adherents of other religions. On the other hand, there are traditions which show the tolerance of the Prophet Muhammad to adherents of other religions. The contradiction between the two themes between coercion and tolerance originating from the same source raises its own versatility in understanding the hadith. This study aims to reveal the meaning of the hadith comprehensively and its relevance in the present context. This research is a descriptive analytic literature study. The data in this study were collected by documentation method to then be managed with the method of analysis ma'ani al-hadith. The research findings state that the hadith commands against non-muslims are spoken in the context of war. The order was aimed at non-muslim parties with the category of ahli harbi. In the present context, this hadith is relevant to the conditions of war